The effect of good corporate governance on earnings management in companies that perform IPO - A.A. Putu Kendran Pramithasari; Gerianta Wirawan Yasa (STIE Perbanas Surabaya, 2016)
Initial Public Offering (IPO) is one of the motivations of the occurrence of earnings management practices. Earnings management is done by a company to obtain a positive response from the market in order to increase the amount of funds. Good corporate go-vernance (GCG) is considered capable of minimizing the measures of earnings manage-ment because it has a goal to achieve a better and healthier company under the principles owned. This study aims to determine the effect of GCG on earnings management in companies that perform IPO. Samples are taken using purposive sampling method and are acquired as many as 31 companies, which are analyzed using multiple linear regres-sions. The result of this study indicates that management ownership, independent com-missioners, and audit committee have negative and significant relationship with earn-ings management, in which this result is consistent with the research hypothesis. Meanwhile, institutional ownership has positive and significant relationship with earn-ings management, in which this result is not consistent with the research hypothesis.